2018
DOI: 10.1038/s41467-018-04698-4
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and evolution of the emerging Pandoraviridae family

Abstract: With DNA genomes reaching 2.5 Mb packed in particles of bacterium-like shape and dimension, the first two Acanthamoeba-infecting pandoraviruses remained up to now the most complex viruses since their discovery in 2013. Our isolation of three new strains from distant locations and environments is now used to perform the first comparative genomics analysis of the emerging worldwide-distributed Pandoraviridae family. Thorough annotation of the genomes combining transcriptomic, proteomic, and bioinformatic analyse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
134
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(146 citation statements)
references
References 51 publications
11
134
1
Order By: Relevance
“…Given the lack of any bcsA domain in the orthologs of the ORF594 in other pandoraviruses and the lack of knowledge on the hypothetical proteins encoded by pandoraviruses, we could alternatively hypothesize that the virus could use for the synthesis of its particles tegument, the gene of the cellulose synthase of A. castellanii (Clarke et al, 2013). In a previous work, it has been shown that when Acanthamoeba was infected with a mimivirus, the transcription of the ameba felt dramatically and at 6 h after infection, the transcription became undetectable (Legendre et al, 2010). We observed herein, that the host gene of cellulose synthase was transcribed during the all the replication cycle of P. massiliensis, showing that the transcription of this amoebal gene is not impacted by the infection with Pandoravirus.…”
Section: Discussionsupporting
confidence: 58%
“…Given the lack of any bcsA domain in the orthologs of the ORF594 in other pandoraviruses and the lack of knowledge on the hypothetical proteins encoded by pandoraviruses, we could alternatively hypothesize that the virus could use for the synthesis of its particles tegument, the gene of the cellulose synthase of A. castellanii (Clarke et al, 2013). In a previous work, it has been shown that when Acanthamoeba was infected with a mimivirus, the transcription of the ameba felt dramatically and at 6 h after infection, the transcription became undetectable (Legendre et al, 2010). We observed herein, that the host gene of cellulose synthase was transcribed during the all the replication cycle of P. massiliensis, showing that the transcription of this amoebal gene is not impacted by the infection with Pandoravirus.…”
Section: Discussionsupporting
confidence: 58%
“…3a ; Supplementary Fig. 1 ) 8 , 44 . With the presence of 10 ancestral NCLDV genes, a number similar to several other NCLDV, the sylvanvirus genome can be considered near complete (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we do expect that the physiological traits shared by these viruses will make their global gene contents qualitatively similar. Members of the same virus family should then appear well clustered in a cladistic analysis/tree [ 51 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prefix “Meta” indicates sequences from nonisolated viruses. A more generic phylogenetic tree placing the Mimiviridae in the context of other large DNA virus families is shown in [ 51 ].…”
Section: Figurementioning
confidence: 99%